2018
DOI: 10.1002/stc.2298
|View full text |Cite
|
Sign up to set email alerts
|

Online control of an active seismic system via reinforcement learning

Abstract: Summary Tuning the seismic control systems in order to achieve optimal performance is a challenging area due to the system and disturbance uncertainties. Although, model uncertainties, process time delay, and actuator dynamics can be considered as typical uncertainties, the main source of uncertainty in a seismic control system comes from the aleatory nature of earthquake disturbances. In this case, tuning of the control system based on a given seismic record may not necessarily result in optimal performance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…From Table 7i, it can be concluded that the structural performance evaluations in mitigation applications usually used ML as a regression model while RL was typically utilized as an effective optimization or control algorithm. It is noted that relatively few ML applications for structural optimization and control under winds have been generated compared to those in earthquake engineering community (e.g., Ghaboussi and Joghataie 1995;Adam and Smith 2008;Jiang and Adeli 2008;Yakut and Alli 2011;Subasri et al, 2014;Khodabandehlou et al, 2018;Khalatbarisoltani et al, 2019;Hayashi and Ohsaki 2020). From Table 7ii, it can be concluded that most social media-informed response applications used ML as a classification model for disaster rescue and relief information dissemination.…”
Section: Mitigation and Responsementioning
confidence: 99%
“…From Table 7i, it can be concluded that the structural performance evaluations in mitigation applications usually used ML as a regression model while RL was typically utilized as an effective optimization or control algorithm. It is noted that relatively few ML applications for structural optimization and control under winds have been generated compared to those in earthquake engineering community (e.g., Ghaboussi and Joghataie 1995;Adam and Smith 2008;Jiang and Adeli 2008;Yakut and Alli 2011;Subasri et al, 2014;Khodabandehlou et al, 2018;Khalatbarisoltani et al, 2019;Hayashi and Ohsaki 2020). From Table 7ii, it can be concluded that most social media-informed response applications used ML as a classification model for disaster rescue and relief information dissemination.…”
Section: Mitigation and Responsementioning
confidence: 99%
“…The existing literature focuses on developing ANN models in active and semi-active control, while more advanced learning algorithms, such as reinforcement learning (Khalatbarisoltani et al, 2019), should be explored to realize robust control in tackling various sources of uncertainties simultaneously, including seismic uncertainties and time delays. Meanwhile, the promise of implementing ML in structural control can be enhanced if other forms of control devices are investigated, such as active tuned mass damper, distributed actuators, and semi-active stiffness dampers (Fisco and Adeli, 2011).…”
Section: Structural Control For Earthquake Mitigationmentioning
confidence: 99%
“…A state predictor is combined with proposed controller to solve the time delay problem. 9 Chen and Lai have combined a transfer system with a modern control strategy for shaking tables in order to mimicking the responses of high-rise buildings subjected to earthquakes. Three nonlinear controllers and three linear controllers are designed and synthesized to verify the feasibility and applicability of the proposed strategy.…”
Section: Introductionmentioning
confidence: 99%